2021
DOI: 10.1186/s12885-020-07710-7
|View full text |Cite
|
Sign up to set email alerts
|

Lutetium oxodotreotide (177Lu-Dotatate) for the treatment of unresectable or metastatic progressive gastroenteropancreatic neuroendocrine tumors: a cost-effectiveness analysis for Scotland

Abstract: Background Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) represent a heterogenous group of tumors. Findings from the phase III NETTER-1 trial showed that treatment of unresectable/metastatic progressive gastrointestinal (GI) NETs with 177Lu-Dotatate resulted in a significant improvement in progression-free survival (PFS) and overall survival (OS) compared with best supportive care (BSC) with high dose octreotide long-acting repeatable (LAR) 60 mg. A health economic analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The response predictors of this novel treatment have not yet been well described in the literature. Moreover, while 177 Lu-Dotatate is reported to be cost-effective at a national level (Smith-Palmer et al 2021 ), the unit cost is sufficiently high to warrant further investigation to identify those most likely to benefit from treatment. In this report, we describe several prognostic factors of adverse outcome and recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…The response predictors of this novel treatment have not yet been well described in the literature. Moreover, while 177 Lu-Dotatate is reported to be cost-effective at a national level (Smith-Palmer et al 2021 ), the unit cost is sufficiently high to warrant further investigation to identify those most likely to benefit from treatment. In this report, we describe several prognostic factors of adverse outcome and recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at each stage along the care pathway, cost-efficiency can be maximised through a comprehensive understanding of the patient population, health system capacity and resources, as well as the most appropriate diagnostic tools, treatments and supportive care interventions. There is some evidence of the cost-effectiveness of specific treatments for NENs, 94,95,[131][132][133][134][135][136][137] and cost-efficiency of care pathways for other conditions has been demonstrated. [13][14][15][16][17][18] It is important to note, however, that there is currently insufficient evidence on the costeffectiveness of many types of NEN management.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses have shown that RLT is a cost-effective alternative to systemic treatment in other cancers such as neuroendocrine tumors. [25][26][27][28] In the diagnostic process, the proPSMA trial has shown the superior diagnostic value of 68 Ga-PSMA-PET compared with conventional imaging in patients with prostate cancer, and it has also proved to be less costly. 29 Besides primary staging, the early detection of metastasis also has a high value in recurrent disease, such as in the setting of oligometastatic disease 30 and in differentiating nonmetastatic from metastatic prostate cancer.…”
Section: Discussionmentioning
confidence: 99%